225k views
2 votes
F(x)=x2–5x+7, find f(3)

User Afessler
by
5.3k points

1 Answer

3 votes

Answer:


f(3) = 1

Explanation:

f(x) = x² - 5x + 7

To find f(3) substitute the value of x that's 3 into f(x) that's replace every x in f (x) by 3

We have


f(3) = {3}^(2) - 5(3) + 7 \\ = 9 - 15 + 7 \\ = - 6 + 7

We have the final answer as


f(3) = 1

Hope this helps you

User Irio
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.